Analisis Efektivitas Komik Digital sebagai Media Dakwah di Akun Instagram @pengenjadibaik - Amaliyah, Walidatul (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Instagram has become an effective platform for spreading dakwah due to its large user base and easy accessibility. One of its innovations is the use of digital comics as a medium for dakwah. The Instagram account @pengenjadibaik is one such dakwah account that utilizes digital comics to convey religious and moral values in an engaging way, without being bound by space and time. The purpose of this research are to understand the presentation of digital comics as a dakwah medium on the @pengenjadibaik Instagram account and evaluate the effectiveness of this dakwah. This research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The data is then analyzed in three stages: data reduction, data presentation, and drawing conclusions. The study concludes that: 1) The dakwah media through digital comics combines text and images that are interrelated. The meaning conveyed aligns with the purpose of creating the comics, which is to invite fellow Muslims to do good deeds and teach values in life. 2) The effectiveness of dakwah is evident from changes in followers, such as improved understanding (cognitive), positive interactions in the form of likes and motivation to migrate (affective), and actions that apply the dakwah message and share content (behavioral), indicating the success of dakwah through digital comics. Penelitian ini memperoleh kesimpulan 1) Media dakwah melalui komik digital menggabungkan teks dan gambar yang saling berhubungan. Makna yang terkandung sesuai dengan tujuan pembuatan komik, yaitu sebagai media untuk mengajak sesama muslim untuk berbuat baik dan mengajarkan nilai-nilai kehidupan. 2) Efektivitas dakwah terlihat dari perubahan pada pengikut, seperti peningkatan pemahaman (kognitif), interaksi positif berupa likes dan motivasi untuk hijrah (afektif), dan tindakan menerapkan pesan dakwah serta berbagi konten (behavioral), yang menunjukkan keberhasilan dakwah melalui komik digital.